Exposure assessment to heavy metals in general population in an area at high environmental risk through biological monitoring. (19th October 2011) - Serinelli, Maria; Bisceglia, Lucia; Vimercati, Luigi; Galise, Ida; Minerba, Sante; Conversano, Michele; Assennato, Giorgio
Abstract : Objectives: In areas at high environmental risk, a major issue is the correct assessment of the exposure of general population to industrial pollutants. The objectives were: to evaluate the exposure to heavy metals emitted from industrial area of Taranto; to correlate biological monitoring data with environmental data, in order to clarify the impact of industrial pollution in terms of internal dose. Methods: A cross sectional study has been designed to measure levels of urinary arsenic, lead, cadmium, chromium, manganese in 300 subjects resident in Taranto and in a rural area. Adult subjects have been selected by a random stratified sampling. Each subject in the study has been asked to sign the informed consent form and has been administered a structured standardised questionnaire to collect personal data in order to control for potential confounders. Results: Preliminary results based on 141 subjects (67 men and 74 women) from the polluted area, show mean concentrations of lead (10.80 ± 8.52 microg/l) and chromium (0.45 ± 0.64 microg/l) exceeding threshold of Italian Society of Reference Values. Conclusions: Results from biological monitoring may enhance to address the issue of preventing harmful effects of environmental factors.